2018
DOI: 10.1371/journal.pone.0202562
|View full text |Cite
|
Sign up to set email alerts
|

Effect of health intervention integration within women's self-help groups on collectivization and healthy practices around reproductive, maternal, neonatal and child health in rural India

Abstract: BackgroundThis study evaluates an eight-session behavior change health intervention with women’s self-help groups (SHGs) aimed to promote healthy maternal and newborn practices among the more socially and economically marginalized groups.MethodsUsing a pre-post quasi-experimental design, a total of 545 SHGs were divided into two groups: a control group, which received the usual microcredit intervention; and an intervention group, which received additional participatory training around maternal, neonatal, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
121
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(130 citation statements)
references
References 42 publications
8
121
1
Order By: Relevance
“…Consistent with findings from studies of similar interventions in other parts of the country [ 20 , 31 ], this study shows significant improvements in health practices in the intervention areas, particularly practices that are one-time point and independent of health care service supplies. In the comparison areas, some maternal and newborn practices also improved, which could be attributed to increased social cohesion and group collectivisation identified in other studies [20] . The results of this study as well as literature reveal that in less developed Indian states, women's exposure to mass media remains low [37][38][39][40] .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Consistent with findings from studies of similar interventions in other parts of the country [ 20 , 31 ], this study shows significant improvements in health practices in the intervention areas, particularly practices that are one-time point and independent of health care service supplies. In the comparison areas, some maternal and newborn practices also improved, which could be attributed to increased social cohesion and group collectivisation identified in other studies [20] . The results of this study as well as literature reveal that in less developed Indian states, women's exposure to mass media remains low [37][38][39][40] .…”
Section: Discussionsupporting
confidence: 54%
“…The concentration indices were computed and Lorenz curves were drawn for maternal health outcomes-ANC visits, check-ups, consumption of IFA tablets, institutional delivery, PNC check-ups and use of contraceptive method-dependent upon supply of services or access to health facilities. Lorenz curves were not drawn for newborn health outcomes-cord care, thermal care and breastfeeding practices-dependent on women's learning and practices, and less dependent on supply side factors [20] . All analyses employed Stata version 13 • 0 (StataCorp, College Station, TX, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Studies highlighted the positive effect of health literacy on improving maternal health utilisation despite low levels of education in communities (31). Community health programs are increasingly providing evidence for reducing maternal and newborn health inequities in rural areas through women's empowerment and support greater female economic participation (32)(33)(34). Additionally, community mobilisation advocates progressively push for layering multiple interventions, including nancial mechanisms in developmental packages for low resource regions seeking to impact maternal mortality (35)(36)(37).…”
Section: Community-based Health Literacy and Micro Nance Programmentioning
confidence: 99%
“…The commonly adopted Roger's model of diffusion has been used in public health programs to describe the pattern of behaviour change adoption across communities using selected interventions such as contraceptive use, child marriage and intimate partner violence (47)(48)(49)(50). Moreover, while previous diffusion studies have shown the key role of interpersonal connection in promoting health information, the application of the model to evaluate the spread of micro nance has not yet been done (32,39,44,50). Particularly, no study elsewhere, to the best of our knowledge, has evaluated the diffusion of the knowledge of maternal danger signs from micro nance members to non-members in a rural setting with low literacy and high poverty-populations.…”
Section: Community-based Health Literacy and Micro Nance Programmentioning
confidence: 99%
See 1 more Smart Citation